Perbedaan Persepsi pada Pengguna Kondom dan MOP (Metode Operasi Pria) di Wilayah Puskesmas Kedungmundu Semarang - Elia Rakhmawati; Kismi Mubarokah (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
The application of the family planning program in the community have been success, but contraceptive usage in female (93,66%) higher than male (6,34%). The male participation was needed to the family planning program especially in using contraceptives. The purpose of the study was to know differences of perceptions about the engagement of male in the family planning program particularly condom and vasectomy use.This is quantitative research with cross sectional approach. The samples were collected by purposive sampling and quota sampling methods; sample was 30 condom users and 30 vasectomy participants. Data has been analyzed by independent t-test.The result of the study showed no difference of perception about the male engagement in the family planning program in condom users and vasectomy participants (p-value 0.11<0.05); both groups hadÂ  good perception in contraception. Only 10% of condom users who have the low perceptin and 6.7% of vasectomy participants had the low perception. These respondents had perception that the involvement of men in family planning by using male contraceptives was embarrassing and unimportant.The sugestion was increasing theÂ  existence of family planning information to increase male perception in family planning participation.Keywords: Perception, Vasectomy, condoms